The Metabolic Syndrome Does Not Affect Development of Collateral Circulation in the Poststenotic Swine Kidney. (9th August 2018) - Zhang, Xin; Kim, Seo Rin; Ferguson, Christopher M; Ebrahimi, Behzad; Hedayat, Ahmad F; Lerman, Amir; Lerman, Lilach O
Abstract: BACKGROUND: The collateral circulation is important in maintenance of blood supply to the ischemic kidney distal to renal artery stenosis (RAS). Obesity metabolic syndrome (MetS) preserves renal blood flow (RBF) in the stenotic kidney, but whether this is related to an increase of collateral vessel growth is unknown. We hypothesized that MetS increased collateral circulation around the renal artery. METHODS: Twenty-one domestic pigs were randomly divided into unilateral RAS fed an atherogenic (high-fat/high-fructose, MetS-RAS) or standard diet, or controls ( n = 7 each). RBF, glomerular filtration rate (GFR), and the peristenotic collateral circulation were assessed after 10 weeks using multidetector computed tomography (CT) and the intrarenal microcirculation by micro-CT. Vascular endothelial growth factor (VEGF) expression was studied in the renal artery wall, kidney, and perirenal fat. Renal fibrosis and stiffness were examined by trichrome and magnetic resonance elastography. RESULTS: Compared with controls, RBF and GFR were decreased in RAS, but not in MetS-RAS. MetS-RAS formed peristenotic collaterals to the same extent as RAS pigs but induced greater intrarenal microvascular loss, fibrosis, stiffness, and inflammation. MetS-RAS also attenuated VEGF expression in the renal tissue compared with RAS, despite increased expression in the perirenal fat. CONCLUSIONS: MetS does not interfere with collateral vessel formation in the stenotic kidney, possibly because decreased renal arterial VEGF expression offsets its upregulation in perirenal fat, arguing against a major contribution of the collateral circulation to preserve renal function in MetS-RAS. Furthermore, preserved renal function does not protect the poststenotic kidney from parenchymal injury.